Adaptive control of a quadrotor with uncertain parameters - Nguyễn, Việt Phương; Nguyễn Duy Khánh; Hồ Công Quốc (Journal of Military Science and Technology, 2023)
This paper presents the results of synthesizing a control law for position tracking and stabilization of an unmanned aerial vehicle (UAV) in the form of a quadrotor, using a speed-gradient method in an adaptive control algorithm that adapts to uncertain changes in parameters. Simulation results in MATLAB/SIMULINK with an assumed quadrotor model demonstrate that using the adaptive controller helps the quadrotor operate stably and track the desired trajectory in cases of uncertain quadrotor parameters.